A randomised, blinded, crossover study to assess the efficacy of a feed supplement in alleviating the clinical signs of headshaking in 32 horses. (19th September 2012) - Talbot, W. A.; Pinchbeck, G. L.; Knottenbelt, D. C.; Graham, H.; Mckane, S. A.
Summary Reasons for performing study: Feed supplements are commonly used by owners to alleviate headshaking; however, randomised, controlled trials are required to assess their efficacy. Objective: To determine the efficacy of a feed supplement for alleviation of the clinical signs of headshaking using a randomised, blinded, placebo‐controlled trial. Methods: Using a crossover design, 44 horses previously diagnosed with chronic idiopathic headshaking received both the supplement and a matching placebo per os for 28 days with a washout period between of 14 days. Video recordings were taken at rest and exercise prior to the study and at the end of both periods of treatment. The degree of headshaking was assessed in a blinded, randomised manner by 2 veterinary surgeons. At the same time points, owners completed a questionnaire to assess the severity of headshaking signs. A Wilcoxon signed rank test was used to compare the scores while on supplement and placebo. Results: Using the video assessments, there was no significant difference between scores while on supplement compared with placebo (P = 0.7). Using the questionnaire responses, there was no significant difference between scores for any activity when the placebo and the supplement were compared with each other. However, owners reported significant improvement during all activities for both placebo and supplement compared with pretreatment scores. Conclusions and potential relevance: The supplement offered no benefit over a placebo in alleviating the clinical signs of headshaking. There appeared to be a significant proxy placebo effect when the outcome was based on subjective owner perception of clinical signs. This study demonstrated no beneficial effect of this supplement on the clinical signs of headshaking. The study did show a significant placebo effect, thereby highlighting the necessity of properly conducted, randomised controlled trials, with blinding, to assess true treatment effects in trials in animals.